Keberadaan Bank Syariah dalam Tata Hukum Nasional (Sharia Faculty Islamic Economic Law Study Department, 2019)
The presence of Islamic banks operating on a profit sharing system is the beginning of the history of the growth of Islamic banks in Indonesia as an effort to meet the needs of the people who want banking products and services that are not interest-based, and are not speculative or not violating the principles of justice and togetherness. In addition, the birth of Islamic banks is also an opportunity for Muslims to use to relate calmly without hesitation because it is based on strong religious motivation in mobilizing public funds to finance economic development towards the welfare of many people. The existence of Islamic banks in the national legal system has a strong foothold after the enactment of Law Number 7 of 1992 concerning Banking which has substantially regulated banking business activities that have an operational basis for profit sharing. Provisions for profit sharing contained in these laws and regulations have been used as the legal basis for the operation of Islamic banks in Indonesia.